Value of animal traceability systems in managing a foot-and-mouth disease outbreak in southwest Kansas - D.L. Pendell; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 2007)
Concerns regarding management of animal disease and related perceptions about food safety have escalated substantially in recent years. Terrorist attacks of September 2001, discovery of bovine spongiform encephalopathy (BSE) in a dairy cow in December 2003 in Washington, subsequent discoveries of BSEinfected animals in Texas in 2005 and Alabama in 2006, and recent worldwide outbreaks of highly contagious animal diseases (i.e., foot-and-mouth disease [FMD] and Avian influenza) have made apparent the need for animal traceability in U.S. livestock production and marketing. In addition, animal identification systems are rapidly developing throughout the world, effectively increasing international trading standards. One way to combat and more quickly arrest spread of contagious diseases is through animal ID. Capability to rapidly identify locations where an animal has been affects the ability to isolate, trace, and arrest spread of a disease. Animal ID systems are rapidly developing throughout the world and the U.S. is behind many other countries in this development. Efforts to develop animal ID systems in the U.S. were launched prior to the initial BSE discovery, but they gained considerable momentum afterwards. The National Animal Identification System is intended to identify specific animals in the U.S. and record their movement over their lifetime. The goal is to enable a 48-hour trace-back of the movements of any diseased or exposed animal. This will limit spread of animal diseases by enabling faster trace-back of infected animals; limit production losses due to disease presence; reduce the costs of government control, intervention, and eradication; and minimize potential international trade losses3. The purpose of this research is to determine the economic implications of increased improvements in animal ID systems in the event of an FMD outbreak in southwest Kansas. Specifically, a disease spread model is used to determine the probable spread of a hypothetical FMD outbreak. Results from the disease-spread model are integrated into an economic framework to determine economic impacts.
Keywords: Cattlemen& #x27; s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; BSE; Foot-and-mouth disease